Prove that $\lim_{n \to\infty} \frac{x_{n+1}}{x_n} = a \implies \lim_{n \to\infty} \sqrt[n]{x_n} = a$. [duplicate]

Given a sequence $(x_n)_{n=1}^\infty$ such that $\forall n: x_n > 0$, prove that

$$\lim_{n \to\infty} \frac{x_{n+1}}{x_n} = a \implies \lim_{n \to\infty} \sqrt[n]{x_n} = a.$$

-

marked as duplicate by vadim123, martini, Thomas, Brandon Carter, Dennis GulkoJul 24 '13 at 15:42

The idea behind this proof is, that for $n$ sufficiently large, given that the ratio of consequent terms of the sequence is very close to $a$, we get $x_{n+1} = ax_n$, that is $x_n = a^n$. Then $\sqrt[n]{x_n} = \sqrt[n]{a^n} = a$.

Proof. Let $\epsilon > 0$. There is $n_0$ such that for all $n \ge n_0$ we have

$$a - \epsilon < \frac{a_{n+1}}{a_n} < a + \epsilon.$$

We can find bounds for $a_n$:

$$a_{n_0}(a - \epsilon)^{n - n_0} \le a_n \le a_{n_0}(a + \epsilon)^{n-n_0}.$$

Taking roots, we obtain

$$\sqrt[n]{a_{n_0}(a - \epsilon)^{n - n_0}} \le \sqrt[n]{a_n \vphantom{()^n} } \le \sqrt[n]{a_{n_0}(a + \epsilon)^{n-n_0}},$$ that is $$\sqrt[n]{a_{n_0} \vphantom{()^n} }{\sqrt[n]{(a - \epsilon)^{n}}}\sqrt[n]{(a - \epsilon)^{-n_0}} \le \sqrt[n]{a_n \vphantom{()^n} } \le \sqrt[n]{a_{n_0} \vphantom{()^n} }{\sqrt[n]{(a + \epsilon)^{n}}}\sqrt[n]{(a + \epsilon)^{-n_0}}.$$

Now we have that

$$\lim_{n \to\infty} {\sqrt[n]{a_{n_0} \vphantom{()^n} }{\sqrt[n]{(a - \epsilon)^{n}}}\sqrt[n]{(a - \epsilon)^{-n_0}}} = a - \epsilon$$

and

$$\lim_{n \to\infty} {\sqrt[n]{a_{n_0} \vphantom{()^n} }{\sqrt[n]{(a + \epsilon)^{n}}}\sqrt[n]{(a + \epsilon)^{-n_0}}} = a + \epsilon.$$

As $\epsilon$ is arbitrary, we get that the desired limit exists and $\lim_{n \to\infty} \sqrt[n]{x_n} = a$.

Is my proof correct? I would like to get any feedback.

-
If anybody knows how to make all \sqrt the same size, please do. – David Čepelík Jul 24 '13 at 13:55
You could try inserting \vphantom{()^n} in the body of the roots that you deem too small. And I think your proof looks fine. – Harald Hanche-Olsen Jul 24 '13 at 14:05
Thank you, @HaraldHanche-Olsen, that worked! – David Čepelík Jul 24 '13 at 14:12
@ Cepelik You should consider three distinct cases seperately for a complete proof. 1. a=0, 2. 0 < a < \infty 3. a = \infty. 2nd case can also be shown using Cauchy's first theorem on limit. – Dutta Jul 24 '13 at 14:39
You need "$x_n$'s", etc., throughout the main body, not "$a_n$'s" – David Mitra Jul 24 '13 at 14:43